Adult training in the digital age - Robert Gold; Eckhardt Bode (Kiel Institute for the World Economy (IfW), 2017)
Digital technologies will both create new jobs and replace existing ones. To cope with increasing labor market dynamics in the digital age, workers will have to become more mobile across jobs, occupations, and industries. The relative importance of their job-specific skills will decrease while that of their general skills applicable to various occupations will increase. The G20 should establish national adult training programs that focus on improving workers' general skills, specifically their theoretical, non-cognitive, and digital skills. These general skills will enable workers to work with technology instead of competing with it, thereby increasing their job mobility and employability.
Keywords: E24; I38; J62; O33; 330; digitalization; employability; job mobility; adult training; skills; G20